Political implications of the Islamic notion of "supersession" as reflected in Islamic jurisprudence - Sachedina, Abdulaziz Abdulhussein (Islam and Christian-Muslim relations, 1996)
The paper undertakes to investigate the ways in which the dominant Muslim community regulated legal‐ethical relations with its non‐Muslim minorities. The ideological underpinnings of the Islamic legal tradition in the area of jihad provided legitimacy for the Muslim political domination of the lands and peoples beyond the original boundaries of Islam. The central argument of the paper is that Muslim jurists were involved in the routinization of the qur'anic message about ‘Islam being the only true religion with God’ (Q. 3:19) in the context of the social and political position of the community. The interaction between the idea of Islam being the universal faith for all humankind and the existing predominance of Muslim political power created the specific legal language that provided the justification to extend the notion of jihad beyond its strictly defensive meaning in the Qur'an to its being an offensive instrument for Muslim creation of a dominant political order.